Creep and Shrinkage Their Effect on the Behavior of Concrete Structures - Rüsch, Hubert; Jungwirth, Dieter; Hilsdorf, Hubert K. (Springer New York, 1983)
This book is based on Reinforced Concrete-Prestressed Concrete, Volume 2, Accounting for the Effects of Creep and Shrinkage on the Behavior of Structural Systems by Hubert Rusch and Dieter Jungwirth, which appeared in German in 1976. Even then, it was Hubert Rusch's fervent wish to have his thoughts on the deformations of concrete translated into English in order to reach a wider audience. His earlier efforts to contribute a study to the Series of Monographs of the Ameri can Institute had unfortunately not succeeded. Despite a serious illness, Hubert Rusch undertook, with his characteristic prudence and thoroughness, the preparatory work for the translation and related revision of his book. Unfortunately fate did not grant him the satisfaction of seeing his work completed. Hubert Rusch died on October 17, 1979. In writing this book, Hubert Rusch drew on his many years of devoted study of the creep problem. These investigations go back to 1934. His awareness of the plastic deformation of concrete under sustained load, which had been reported to him on the occasion of an American sojourn, led him to discover the causes of a major building collapse. At his urging, Professor A. Hummel published, in 1935, a critical survey of the test results then available on concrete creep